2017
DOI: 10.1186/s12867-017-0086-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable reference genes for real-time quantitative PCR analysis of hydrogen peroxide-treated human umbilical vein endothelial cells

Abstract: BackgroundOxidative stress can induce cell injury in vascular endothelial cells, which is the initial event in the development of atherosclerosis. Although quantitative real-time polymerase chain reaction (qRT-PCR) has been widely used in gene expression studies in oxidative stress injuries, using carefully validated reference genes has not received sufficient attention in related studies. The objective of this study, therefore, was to select a set of stably expressed reference genes for use in qRT-PCR normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In accordance with previous studies, they identified HPRT1 and YWHAZ as the two most suitable genes in HUVEC-stain treated cells stimulated with TNF- α in relation to gene expression [ 25 ]. However, there was complete discrepancy in two recent studies, which identified TFRC, RPLO, GAPDH, and ACTB as the most stable genes [ 12 ] and the other studies found that hmbs, ywhaz, and tbp were considered as three most stable RGs in MSCs before and after differentiation [ 54 ]. Interestingly, in our study, ywhaz was ranked 1 st , hmbs 3 rd , actb 7 th , tfrc 8 th , gapdh11 th , and rplo 9 th , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with previous studies, they identified HPRT1 and YWHAZ as the two most suitable genes in HUVEC-stain treated cells stimulated with TNF- α in relation to gene expression [ 25 ]. However, there was complete discrepancy in two recent studies, which identified TFRC, RPLO, GAPDH, and ACTB as the most stable genes [ 12 ] and the other studies found that hmbs, ywhaz, and tbp were considered as three most stable RGs in MSCs before and after differentiation [ 54 ]. Interestingly, in our study, ywhaz was ranked 1 st , hmbs 3 rd , actb 7 th , tfrc 8 th , gapdh11 th , and rplo 9 th , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse-transcription-qPCR is one of the most widely used methods directly evolved from the end-point detection PCR to detect gene expression level under different research conditions because of its time-saving, high sensitivity, and specificity [ 12 14 ]. But if this technique is performed in an inappropriate way, especially using incorrect housekeeping genes (HKGs), considerable misinterpretation of results will happen [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…BrightGreen qPCR MasterMix-Low ROX and a Bio-Rad CFX96 were used for performing the qPCR. Primers for TATA-box binding protein (TBP) and Peptidylprolyl isomerase A (PPIA) were used as internal controls as previously described [ 34 ]. ZIKV primers were designed for this work with the following sequences: Forward 5′-CAAAAGGAGGCCCTGGTCAT-3′, Reverse 5′-ATGAAAGACGTCCACCCCAC-3′ (92 bp product).…”
Section: Methodsmentioning
confidence: 99%
“…Their findings regard one cell type with different biological replicates, and with the variability of expression, the ranking by three programs produced different results [58], thus proving that in terms of reference gene identification, using three programs is fully justified. Similarly, in identifying housekeeping genes in HUVECs treated with hydrogen peroxide, RPLP0 was shown to be among the most stable genes, however in our study, this candidate was found to be the least stable gene [59].…”
Section: Analysis Of Candidate Housekeeping Gene Stabilitymentioning
confidence: 43%